Antimicrobial resistance profiles of bacteria from clinical specimens at Amhara Public Health Institute, Bahir Dar, Ethiopia: A retrospective study - Michael Getie; Wudu Tafere; Alem Tsega; Tsehaynesh Gebreyesus; Gizeaddis Belay; Alemayehu Abate; Hailu Getachew; Bayeh Abera; Demeke Endalamaw; Tazeb Molla; Teshiwal Deress; Belay Bezabih (PLoS ONE, 2025)
Background Antimicrobial resistance is a major public health problem worldwide, particularly in developing countries. The effectiveness of currently available antimicrobial is decreasing due to the increasing prevalence of resistant strains among bacterial isolates. This study aims to determine the antimicrobial resistance profile of bacterial isolates from different clinical specimens at Amhara Public Health Institute. Materials and methods A retrospective analysis was conducted using data extracted from the WHONET 2024 database from July 1, 2022, to December 31, 2024, at the Amhara Public Health Institute bacteriology and mycology reference laboratory. The age range of the patients included in this study was 1–96 years, and the mean age of the patients was 33.44 ± 17.36 years. The data included demographic characteristics of patients, types of bacterial isolates and antimicrobial resistance profiles, which were analyzed using SPSS version 20 statistical software. The descriptive statistics were displayed as percentages and frequencies. The chi-square test was used to determine the prevalence of bacterial isolates from patients by age and sex. P-values below 0.05 were seen as a sign of a statistically significant difference. Results A total of 1165 specimens were processed, resulting in a culture-positive rate of 41% (478/1165) for bacterial pathogens isolated from clinical specimens. The majority of bacterial isolates were from stool (55%; 263/478), urine (20%; 96/478), wound (12.9%; 62/478), and blood (9.8%; 45/478), respectively. Of these, Gram-negative bacteria accounted for 89.1% (426/478) and Gram-positive bacteria accounted for 10.8% (52/478). The predominant bacterial isolates were Vibrio cholerae 54.6% (261/478), E. coli 16.1% (77/478), Klebsiella spp 6% (29/478), S. aureus 4.6% (22/478) and Enterococcus spp 2.9% (14/478). In this study Proteus spp 67.6% (46/68), A. baumannii 58.4% (31/53), and Klebsiella spp 64.1% (136/212) were identified as the most resistant bacteria to the tested antimicrobial. S. aureus shows resistance to tobramycin 100% (1) and penicillin 100% (17), oxacillin 84.6% (11/13) and tetracycline 63.6% (7/11). Enterococcus spp resistance to vancomycin 85.7% (6/7), penicillin 72.7% (8/11) and ampicillin 62.5% (5/8). In total, 53.1% (254/478) of the bacterial isolates were classified as multidrug-resistant (MDR), with 93.7% (238/ 254) being Gram-negative bacteria. Conclusions Both Gram-negative and Gram-positive isolates showed high levels of resistance to commonly used antimicrobial. To address the problem of antimicrobial resistance, healthcare providers should focus on responsible antimicrobial prescribing practices based on local antibiogram data.